Patients with xeroderma pigmentosum complementation groups C, E and V do not have abnormal sunburn reactions. (December 2013) - Sethi, M.; Lehmann, A.R.; Fawcett, H.; Stefanini, M.; Jaspers, N.; Mullard, K.; Turner, S.; Robson, A.; McGibbon, D.; Sarkany, R.; Fassihi, H.
Summary Background Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder of DNA repair. It is divided into eight complementation groups: XP‐A to XP‐G (classical XP) and XP variant (XP‐V). Severe and prolonged sunburn reactions on minimal sun exposure have been considered a cardinal feature of classical XP. However, it has recently become clear that not all patients have abnormal sunburn reactions. Objectives To examine sunburn reactions in a cohort of patients with XP and correlate this to the complementation group. Methods Sixty patients with XP attending the U.K. National XP Service from 2010 to 2012 were studied. Their history of burning after minimal sun exposure was assessed using a newly developed sunburn severity score. The age at which the first skin cancer was histologically diagnosed in each patient, and the presence of any neurological abnormality, was also recorded. Results Sunburn severity scores were abnormally high in patients with XP‐A, XP‐D, XP‐F and XP‐G compared with non‐XP controls. There was no significant difference in sunburn score of patients with XP‐C, XP‐E and XP‐V compared with controls (P > 0·05). Patients with XP‐C, XP‐E and XP‐V were more likely to have skin cancer diagnosed at an earlier age than those with severe sunburn on minimal sun exposure. In addition, patients with XP with severe sunburn had an increased frequency of neurological abnormalities. Conclusions Not all patients with XP have a history of severe and prolonged sunburn on minimal sun exposure. The normal sunburn response of patients with XP‐C, XP‐E and XP‐V may relate to the preservation of transcription‐coupled DNA repair in these groups. Those with a history of severe sunburn on minimal sun exposure developed their first skin cancer at an older age compared with patients with XP‐C, XP‐E and XP‐V, but they had an increased frequency of neurological abnormalities. Physicians need to be aware that about half of all patients with XP will present without a history of abnormal sunburn.